Analisis Determinasi Kinerja Pemerintah (Studi Kasus Pada Badan dan Dinas di Kabupaten Jember) - Lalinda, Erica Efif; Ardhiarisca, Oryza (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2024)
This research aims to analyze and explain the effect of implementing performance-based budgeting, accuracy of budget targets and internal control on the performance of The Jember Regency goverenment. This research is a quantitative research. The population of this research is all regional apparatus including Agencies, Departments, Districts, Inspectorates, DPRD Secretariat and Regional Secretariat in Jember Regency. The sampling technique in this research used a purposive sampling method, with collaboration between the Department and Agency so that a sample of 23 Departments and 6 Agencies was obtained with a total of 87 respondents. The data source in this research is primary data using a questionnaire with a Likert scale. The statistical tool used to test the hypothesis is the IBM Statistics 21 application. The results of the analysis show that independent variables partially or simultaneously, namely the implementation of performance-based budgeting, budget targets and internal control, have a significant effect on the performance of the Jember Regency government.